Harnessing the Power of Secure and Scalable Generative AI : A Deep Dive into AWS and SAP’s Cutting-Edge Collaboration - Lakshmi Srinivasa Rao Gogula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the groundbreaking collaboration between Amazon Web Services (AWS) and SAP in developing secure and scalable generative AI solutions for businesses. It examines the critical need for robust AI implementations in the face of growing security and scalability challenges, highlighting the unique strengths that AWS and SAP bring to their partnership. The article delves into real-world applications across industries, discusses key benefits for businesses including operational efficiency and enhanced decision-making, and outlines implementation strategies and best practices. Finally, it looks ahead to emerging trends and the long-term vision for AI in business, emphasizing how the AWS-SAP collaboration is poised to shape the future of enterprise AI.